IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING NARRATIVE TEXT THROUGH CUBING TECHNIQUE - Chalish, Qolbi; Siregar, Masitowarni (Universitas Negeri Medan, 2013)
ABSTRACTThis study aims at improving the studentsŸ achievement in writing narrative text through cubing technique. The underlying objective of this study is to investigate whether teaching narrative by applying cubing technique potentially improves studentsŸ skill. The research was conducted by using Classroom Action Research (CAR). The population was the 2012-2013 eleven grade students of SMA Negeri 3 Binjai. The number of students was 42, consisting of females and males. The procedure of the research was administrated into two cycles where each cycle consisted of three meetings. Each meeting included four steps namely: planning, action, observation, and reflection. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the qualitative data was the writing of narrative test while the qualitative data were gathered by using interview, diary notes and observation sheet. Based on the data analysis, the mean of studentsŸ score in Test I was 61.85; for the Test II was 73.85, and for the Test III was 80. The qualitative data showed that the students were interested in the applying of cubing technique. The conclusion is that the application of cubing technique in writing narrative improves the studentsŸ achievement in writing narrative.Keywords: achievement, writing, narrative, cubing technique